Design energy recovery systems with confidence - use pinch technology targets. - Wood, R.M (Philippine Engineering Journal)
In designing a network of heat exchangers for the recovery of waste heat, there is usually a "pinch" at which the minimum approach temperature difference limits energy recovery. Pinch technology emphasizes the importance of utility and other targets, which are independent of the network design, and thus allow a very useful comparison with the requirements of actual networks. Methods for determining utility and area targets are surveyed. These can be applied both to new designs as well as for determining the scope for energy conserving retrofits. It is pointed out that significant improvements in utility targets can often be achieved by appropriate exploitation of process flexibility. Thus, it is essential that for a successful application of these techniques, experts in the technology working closely with personnel who are also experts in the processes being studied are required.